2006
DOI: 10.1353/dem.2006.0031
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parents’ marital quality on adult children’s attitudes toward marriage and its alternatives: Main and moderating effects

Abstract: Drawing on a panel study of parents and children, we investigate linkages between parents' marital quality and adult children's attitudes toward a range of family issues, including premarital sex, cohabitation, lifelong singlehood, and divorce. We hypothesize that parents' marital quality will be negatively related to children's support for these behaviors in adulthood and that parents' marital quality will condition the intergenerational transmission of attitudes toward these issues. We find some evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
4
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 23 publications
(22 reference statements)
3
58
4
3
Order By: Relevance
“…A potential explanation for the difference in findings between their study and ours is that satisfaction with family life is an evaluative indicator of experience in the parental family, whereas we used more objective indicators. Cunningham and Thornton (2006) found that high quality of the parents' marriage, as reported by mother and child, strengthens intergenerational transmission of attitudes towards marriage. This might also be considered as being inconsistent with our results, but it seems reasonable to suppose that marital quality is more directly related to attitudes towards marriage than to fertility behaviour.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A potential explanation for the difference in findings between their study and ours is that satisfaction with family life is an evaluative indicator of experience in the parental family, whereas we used more objective indicators. Cunningham and Thornton (2006) found that high quality of the parents' marriage, as reported by mother and child, strengthens intergenerational transmission of attitudes towards marriage. This might also be considered as being inconsistent with our results, but it seems reasonable to suppose that marital quality is more directly related to attitudes towards marriage than to fertility behaviour.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…Duncan et al's suggestion that satisfaction with family of origin leads to a stronger influence of number of siblings on number of children received support from studies conducted in the 1960s and 1970s (Westoff and Potvin 1967;Hendershot 1969;Bumpass and Westoff 1970;Johnson and Stokes 1976), but does not seem to have received much attention in recent literature. However, Cunningham and Thornton (2006) found that attitudes towards marriage and its alternatives were more strongly transmitted from parents to children if the quality of the parents' relationship was high. Studies on intergenerational transmission of age at first birth did not include satisfaction with family.…”
Section: Theory and Previous Researchmentioning
confidence: 96%
“…Moreover, parents' own family experiences shape parental preferences for their children's family trajectories. Several studies have reported that divorced parents and their children are more tolerant toward nontraditional family forms (Axinn and Thornton 1996;Cunningham and Thornton 2006). However, even though value transmission in families of separation is weaker than in intact families, parental preferences still affect their children's attitudes (van der Valk et al 2008).…”
Section: Parental Marital History and Early Childhood Family Structurementioning
confidence: 99%
“…The existing literature in sociology or/and psychology also concludes that growing up in a divorced family can instill less unfavorable attitudes toward divorce in offspring (Amato, 1988;Axinn & Thornton, 1996;Cunningham & Thornton, 2006;Greenberg & Nay, 1982;Kapinus, 2004;Trent & South, 1989). This result may, at least partly, be explained by the intergenerational transmission of attitudes toward divorce as documented by Axinn and Thornton (1996) or Kapinus (2004).…”
Section: On the Role Of Culture In The Transmission Of Divorce Patternsmentioning
confidence: 97%